2022
DOI: 10.1111/mec.16663
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Grauer's gorilla populations differ in diet and gut microbiome

Abstract: The animal gut microbiome has been implicated in a number of key biological processes, ranging from digestion to behaviour, and has also been suggested to facilitate local adaptation. Yet studies in wild animals rarely compare multiple populations that differ ecologically, which is the level at which local adaptation may occur. Further, few studies simultaneously characterize diet and gut microbiome from the same sample, despite their probable interdependence. Here, we investigate the interplay between diet an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 172 publications
0
7
0
Order By: Relevance
“…Michel et al. (2022) use metabarcoding methods to investigate the interplay between diet and gut microbiome in several geographically isolated and genetically differentiated populations of the critically endangered Grauer's gorilla. They showed marked differences in the composition (though not richness or evenness) of the diet and gut microbiome of genetically differentiated populations, associated with social, ecological, and geographic factors.…”
Section: Cross‐scale Interactions and Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Michel et al. (2022) use metabarcoding methods to investigate the interplay between diet and gut microbiome in several geographically isolated and genetically differentiated populations of the critically endangered Grauer's gorilla. They showed marked differences in the composition (though not richness or evenness) of the diet and gut microbiome of genetically differentiated populations, associated with social, ecological, and geographic factors.…”
Section: Cross‐scale Interactions and Microbiomesmentioning
confidence: 99%
“…Several studies examined questions involved in the interaction between animals and their microbiome, looking at the effects of the microbiome on diet and niche. Michel et al (2022) 2022) examined the combined impact of diet and environmental disturbance (salinity and antibiotics) on the gastrointestinal microbiome of aquatic gastropods. The results showed that a transition to salinity led to lower gut community richness and higher host viability, but only when there was an increase in bacterial generalists in the gut.…”
Section: Cross -Sc Ale Inter Ac Ti On S and Microb Iome Smentioning
confidence: 99%
“…Several studies examined questions involved in the interaction between animals and their microbiome, looking at the effects of the microbiome on diet and niche. Michel et al (2022) used metabarcoding methods to investigate the interplay between diet and gut microbiome in several geographically isolated and genetically differentiated populations of the critically endangered Grauer's gorilla.They showed marked differences in the composition (though not richness or evenness) of the diet and gut microbiome of genetically differentiated populations, associated with social, ecological, and geographic factors. Manthey et al (2022) tested the hypothesis that the holometabolous insect gut microbiota rapidly remolds during metamorphosis, allowing exploration of novel niches during their ontogenesis.…”
Section: Cross Scale Interactions and Microbiomesmentioning
confidence: 99%
“…Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes ‘papers that highlight the power of high‐throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary ‐omics data types and/or models/theory to infer overall ecosystem processes’ (Gillespie et al., 2023). The impressive collection of 44 manuscripts covers a wide range of topics: community assembly processes (Andujar et al., 2022; Arjona et al., 2022; Emerson et al., 2022; Govender et al., 2022; Guerrieri et al., 2022; Ip, Chang, Oh, et al., 2022; Kiemel et al., 2022; Li et al., 2022; Macheriotou et al., 2023; Menéndez‐Serra et al., 2023; Nappi et al., 2022; Noguerales et al., 2023; Overcast et al., 2023; Pino et al., 2023; Van der Loos et al., 2022; Wang et al., 2022), interaction networks (Ando et al., 2022; Bell et al., 2022; Dürrbaum et al., 2022; Encinas‐Viso et al., 2022; Ficetola & Taberlet, 2023; Graham et al., 2022; Ip, Chang, Tun, et al., 2022; Lowe et al., 2022; Lu et al., 2022; Lue et al., 2022; Pitteloud et al., 2022; Srivathsan et al., 2022; Tommasi et al., 2022), cross‐scale interactions and microbiomes (Brinker et al., 2022; Câmara dos Reis et al., 2022; Hu et al., 2022; Kivistik et al., 2022; Manthey et al., 2022; Merges et al., 2022; Michel et al., 2022; Molina et al., 2022; Navine et al., 2022; Pereira et al., 2022; Perez‐Lamarque & Morlon, 2022; Rolshausen et al., 2022), and invasive species/homogenization (Andrés et al., 2023; Graham et al., 2022; Hampel et al., 2022; Kennedy et al., 2022; Overcast et al., …”
Section: Highlights Of 2023mentioning
confidence: 99%